Evaluation of Bone Height and Bone Mineral Density Using Cone Beam Computed Tomography After Secondary Bone Graft in Alveolar Cleft. Issue 5 (July 2015) - Zhang, Dai-zun; Xiao, Wen-lin; Zhou, Rong; Xue, Ling-fa; Ma, Long
<x xml:space="preserve">Abstract</x> Abstract The purpose of this study was to assess the optimal timing of subsequent dental implant placement and orthodontics after alveolar bone grafting (ABG) in patients with unilateral complete clefts of the alveolar process. Iliac bone graft surgery was performed on 60 patients. Bone mineral density (BMD) and height of the ABG areas were assessed using cone beam computed tomography at 3 and 6 months postoperatively. The heights of the labial and palatal bone graft areas were classified using the modified Bergland classification. The study found that there was no change in BMD between 3 months (mean ± SD: 406.51 ± 71.28 Hounsfield units [HU]) and 6 months (409.53 ± 46.37 HU; P = 0.381). Significant changes in the distribution of bone height classifications were observed in the labial and palatal sides of the ABG between 3 and 6 months (P = 0.025 for labial bone height, P = 0.008 for palatal bone height). These results indicate that the alveolar density remained stable between 3 and 6 months, whereas bone height level declined during that period after ABG, the latter indicating bone graft absorption over time. It is, therefore, suggested that subsequent orthodontic or dental implants be placed 3 months after ABG rather than at 6 months or later.